Analysis of Factors Improving Green Process Innovation Performance in Batik Lasem SME”™s - Luthfia, Irin Mirrah; Setyawan, Nanang Adie; Pradita, Arisha Putri (Politeknik Negeri Semarang, 2025)
Business continuity is an interesting phenomenon to study. Because businesses have very intense competition. Innovation is needed in order to continue to exist and develop, the application of strategies that have an impact on the environment is highly expected by consumers today with the rampant health issues that haunt society. The purpose of this study is to build Green Process Innovation Performance from Green Supply Chain Management based on Green Intellectual Capital which is described by Green Human Capital, Green Organizational Capital, Green Relational Capital. The population of this study were the actors of Batik Tulis Lasem SMEs in Rembang Regency. While the sampling technique used in this study is the Census Method. For the number of research samples is 100 samples from the total population of respondents. This research technique uses two approaches: 1). Confirmatory factor analysis, in Structural Equation Modeling (SEM); and 2). Regression Weight on Structural Equation Modeling (SEM). The model output in this study can provide a positive contribution for Batik Tulis Lasem business actors in an effort to be able to realize the continuity and sustainability of their business in environmental aspects, both in the form of managerial implication suggestions and the formulation of scientific articles and measurement instruments. Managerial advice is aimed at the local government in formulating program policies to maintain the existence of entrepreneurs